PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH - Mariyanto, Joko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
The purpose of this study was to analyze the significance of the influence of local taxes and levies partially or simultaneously on revenue at district / town in Central Java Province 2009 - 2013. The results were obtained conclusion: Local tax positive and significant impact on revenue, it indicates that the local tax is the most dominant component on revenue, so the local tax revenue must be continuously improved by optimization of tax collection through the intensification and extension of tax area. Levies positive and significant impact on revenue, this shows that retribution is an important component in the increase in revenue. Local taxes and levies positive and significant impact on revenue, this shows that the local government through local taxes and levies should be increased by means of closely monitoring any tax or levy to be more efficient so as the government and regional development can goes well. Keywords: local taxes, levies, local revenue